Economic organization of medicine and the Committee on the Costs of Medical Care. - Perkins, B B (1998)
Recent strategies in managed care and managed competition illustrate how health care reforms may reproduce the patterns of economic organization of their times. Such a reform approach is not a new development in the United States. The work of the 1927-1932 Committee on the Costs of Medical Care exemplifies an earlier effort that applied forms of economic organization to medical care. The committee tried to restructure medicine along lines consistent with its economic environment while attributing its models variously to science, profession, and business. Like current approaches, the committee's reports defined costs as the major problem and business models of organization as the major solution. The reports recommended expanded financial management and group medicine, which would include growth in self-supporting middle-class services such as fee clinics and middle-rate hospital units. Identifying these elements as corporate practice of medicine, the American Medical Association-based minority dissented from the final report in favor of conserving individual entrepreneurial practice. This continuum in forms of economic organization has limited structural reform strategies in medicine for the remainder of the century.